Coarse aggregate ultra-high performance concrete gradient structure and preparation method thereof

CN117964300BActive Publication Date: 2026-10-27CHINA RAILWAY MAJOR BRIDGE ENG GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410020941.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-05
Publication Date
2026-10-27
Estimated Expiration
2044-01-05

AI Technical Summary

Technical Problem

[0005]本申请提供一种粗骨料超高性能混凝土梯度结构及其制备方法,以解决相关技术中存在的过高的粗骨料掺量会导致混凝土的工作性能和力学性能大幅下降的技术问题

Benefits of technology

[0030]本申请的粗骨料超高性能混凝土梯度结构及其制备方法,通过将第一超高性能混凝土和第二超高性能混凝土的优异性能相结合,使粗骨料超高性能混凝土梯度结构既具有良好的力学性能和工作性能,又具有良好的体积稳定性和抗冲磨性能,通过隔离层使其两侧的第一超高性能混凝土和第二超高性能混凝土充分的触变融合,提升两侧混凝土浆料间的界面粘结性能,保障结构的整体性和性能梯度性,此外,还极大程度上降低制造成本,有利于实现经济效益与实用性能协同提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117964300B_ABST
    Figure CN117964300B_ABST
Patent Text Reader

Abstract

The application relates to a coarse aggregate ultra-high performance concrete gradient structure and a preparation method thereof, and relates to the technical field of building materials and structures.The coarse aggregate ultra-high performance concrete gradient structure comprises, in sequence, a first ultra-high performance concrete layer, an isolation layer and a second ultra-high performance concrete layer.The first ultra-high performance concrete layer comprises a first skeleton formed by coarse aggregate and first ultra-high performance concrete embedding the first skeleton.The second ultra-high performance concrete layer comprises a second skeleton formed by coarse aggregate and second ultra-high performance concrete embedding the second skeleton.The application combines the excellent performance of the first ultra-high performance concrete and the second ultra-high performance concrete, so that the coarse aggregate ultra-high performance concrete gradient structure has good mechanical performance, working performance, volume stability and impact resistance, and the manufacturing cost is greatly reduced, and the economic benefit and practical performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of building materials and structural technology, specifically to a coarse aggregate ultra-high performance concrete gradient structure and its preparation method. Background Technology

[0002] Currently, Ultra-High Performance Concrete (UHPC) is one of the most innovative technologies in the field of concrete materials in recent years. Due to its excellent strength, superior toughness, outstanding durability, and other advantages, it has been widely used in long-span bridges, high-rise buildings, and other projects with high requirements for component performance. However, its special material design results in excessively high amounts of cementitious materials and high material costs. Furthermore, in some UHPC structures, the extensive use of steel fibers can lead to excessive performance margins in certain areas, significantly increasing the overall structural material cost and severely hindering its practical application.

[0003] In related technologies, adding coarse aggregate to UHPC can significantly reduce its total material cost and improve UHPC's elastic modulus, volume stability, and crack resistance.

[0004] However, when the coarse aggregate content in coarse aggregate UHPC exceeds 30%, the excessive coarse aggregate content will lead to a significant decrease in the workability and mechanical properties of the concrete. Summary of the Invention

[0005] This application provides a gradient structure for ultra-high performance concrete with coarse aggregate and its preparation method, in order to solve the technical problem in related technologies that excessive coarse aggregate content can lead to a significant decrease in the workability and mechanical properties of concrete.

[0006] In a first aspect, this application provides a coarse aggregate ultra-high performance concrete gradient structure, which sequentially comprises:

[0007] The first ultra-high performance concrete layer includes a first skeleton formed of coarse aggregate and a first ultra-high performance concrete layer that encapsulates the first skeleton.

[0008] Isolation layer;

[0009] The second ultra-high performance concrete layer includes a second skeleton formed of coarse aggregate and a second ultra-high performance concrete layer that encapsulates the second skeleton.

[0010] In some embodiments, the coarse aggregate has a hardness ≥6, a compressive strength ≥150MPa, a gradation of 15-25mm continuous gradation, and a needle-like and flaky content of 2-8%.

[0011] The aforementioned isolation layer is made of wire mesh, and the mesh diameter is less than or equal to 60% of the minimum diameter of the aggregate.

[0012] In some embodiments, the coarse aggregate content of the first skeleton is less than that of the second skeleton, and the coarse aggregate of both the first and second skeletons is cubically loosely packed, with a skeleton structure void diameter greater than or equal to 8 mm.

[0013] In some embodiments, the first ultra-high performance concrete, by weight, comprises:

[0014] 900-1200 parts cementitious material, 700-1300 parts sand, 10-15 parts shrinkage reducer, 15-30 parts expansion agent, 20-50 parts water reducer, 175-215 parts water, and 150-350 parts steel fiber.

[0015] In some embodiments, the second ultra-high performance concrete, by weight, comprises:

[0016] 900-1200 parts cementitious material, 700-1300 parts sand, 10-15 parts shrinkage reducer, 15-30 parts expansion agent, 30-50 parts water reducer, 170-205 parts water, and 5-40 parts steel fiber.

[0017] In some embodiments, the steel fibers are short, straight steel fibers with a diameter of 0.15mm-0.25mm and a length less than or equal to 80% of the diameter of the corresponding skeleton structure voids.

[0018] Secondly, this application provides a method for preparing the above-mentioned coarse aggregate ultra-high performance concrete gradient structure, comprising the following steps:

[0019] An isolation layer is placed inside the precast mold, and coarse aggregate is piled up on both sides of the isolation layer to form the first skeleton and the second skeleton.

[0020] First ultra-high performance concrete and second ultra-high performance concrete were prepared respectively;

[0021] After placing a perforated plate on the top of the precast mold, the first ultra-high performance concrete and the second ultra-high performance concrete are injected into the precast molds on both sides of the isolation layer in stages through conduits to form the first ultra-high performance concrete layer and the second ultra-high performance concrete layer.

[0022] In some embodiments, when the first ultra-high performance concrete and the second ultra-high performance concrete are simultaneously injected into the pre-cast test molds on both sides of the isolation layer through conduits in stages, the method further includes:

[0023] During each injection, the height difference between the concrete on both sides of the isolation layer should be less than or equal to 120% of the maximum diameter of the coarse aggregate;

[0024] Each injection of concrete should be less than or equal to 30% of the total height, and the interval between two injections should be greater than 3 minutes.

[0025] In some embodiments, the above-mentioned conduit is a pressure hose;

[0026] During the first concrete injection, the height of the outlet of the aforementioned pressure hose from the bottom surface of the precast mold should be greater than or equal to 90% of the maximum diameter of the coarse aggregate.

[0027] During each subsequent injection, the height of the outlet of the aforementioned pressure hose from the top surface of the previously injected concrete shall be greater than or equal to 90% of the maximum diameter of the coarse aggregate.

[0028] In some embodiments, prior to piling up the coarse aggregate, the following steps are also included:

[0029] Alkaline silica sol is evenly sprayed onto the surface of coarse aggregate using a sprayer to perform surface treatment on the coarse aggregate.

[0030] The coarse aggregate ultra-high performance concrete gradient structure and its preparation method of this application combine the excellent properties of the first ultra-high performance concrete and the second ultra-high performance concrete, so that the coarse aggregate ultra-high performance concrete gradient structure has not only good mechanical properties and workability, but also good volume stability and impact and abrasion resistance. The isolation layer enables the first ultra-high performance concrete and the second ultra-high performance concrete on both sides to fully thixotropically fuse, improves the interfacial bonding performance between the concrete slurry on both sides, ensures the integrity and performance gradient of the structure, and greatly reduces the manufacturing cost, which is conducive to achieving a synergistic improvement in economic benefits and practical performance. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0032] Figure 1 This is a schematic diagram of the gradient structure of ultra-high performance concrete with coarse aggregate in Example 1;

[0033] Figure 2 The compressive strength development diagrams are for Example 1 and Comparative Examples 1-4;

[0034] Figure 3 The diagrams show the development of flexural strength for Example 1 and Comparative Examples 1-4;

[0035] Figure 4 The tensile strength development diagrams are for Example 1 and Comparative Examples 1-4;

[0036] Figure 5 This is a schematic diagram of the gradient structure of ultra-high performance concrete with coarse aggregate in Example 4;

[0037] Figure 6 The compressive strength development diagrams are for Example 4 and Comparative Examples 5-8;

[0038] Figure 7 The diagrams show the development of flexural strength in Example 4 and Comparative Examples 5-8.

[0039] Figure 8 The tensile strength development diagrams are for Example 4 and Comparative Examples 5-8.

[0040] In the picture:

[0041] 1. First ultra-high performance concrete layer; 2. Second ultra-high performance concrete layer; 3. Wire mesh; 4. Crushed stone; 5. Steel fiber; 6. Porous iron plate. Detailed Implementation

[0042] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present application, and not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present application.

[0043] This application provides a gradient structure for ultra-high performance concrete with coarse aggregate, which can solve the technical problem in related technologies that the amount of coarse aggregate will lead to a significant decrease in the workability and mechanical properties of concrete.

[0044] The coarse aggregate ultra-high performance concrete gradient structure in this embodiment includes, in sequence, a first ultra-high performance concrete layer, an isolation layer, and a second ultra-high performance concrete layer.

[0045] The aforementioned first ultra-high performance concrete layer includes a first skeleton formed of coarse aggregate and a first ultra-high performance concrete layer that encapsulates the first skeleton.

[0046] The aforementioned second ultra-high performance concrete layer includes a second skeleton formed by coarse aggregate and a second ultra-high performance concrete layer that encapsulates the second skeleton.

[0047] In this embodiment, the superior properties of the first ultra-high performance concrete and the second ultra-high performance concrete are combined, so that the coarse aggregate ultra-high performance concrete gradient structure has good mechanical properties and workability, as well as good volume stability and impact resistance. It can also greatly reduce manufacturing costs and is conducive to achieving a synergistic improvement in economic benefits and practical performance.

[0048] In some embodiments provided in this application, the coarse aggregate has a hardness ≥6, a compressive strength ≥150MPa, a gradation of 15-25mm continuous gradation, and a needle-like and flaky content of 2-8%.

[0049] Preferably, the aforementioned isolation layer is a wire mesh, and the mesh diameter of the wire mesh is less than or equal to 60% of the minimum diameter of the aggregate.

[0050] In this embodiment, the isolation layer provides a stable framework for the first and second skeletons with coarse aggregate stacked in a graded manner on both sides. On the other hand, it allows the first and second ultra-high performance concretes on both sides to fully fuse thixotropically, improving the interfacial bonding performance between the concrete slurries on both sides and ensuring the integrity and performance gradient of the structure.

[0051] In some embodiments provided in this application, the coarse aggregate content of the first skeleton is less than that of the second skeleton, and the coarse aggregate of both the first and second skeletons is cubically loosely packed, and the void diameter of the skeleton structure is greater than or equal to 8 mm.

[0052] In this embodiment, the coarse aggregate content exhibits a gradient distribution perpendicular to the pouring direction, and the coarse aggregate packing model, calculated by Diamond software, is a cubic least dense packing. High-strength coarse aggregate is used, and computer software is employed to design the least dense packing structure of the coarse aggregate, maximizing the amount of coarse aggregate while ensuring good stability and mobility of the coarse aggregate skeleton structure.

[0053] In some embodiments provided in this application, the aforementioned first ultra-high performance concrete, by mass parts, comprises:

[0054] 900-1200 parts cementitious material, 700-1300 parts sand, 10-15 parts shrinkage reducer, 15-30 parts expansion agent, 20-50 parts water reducer, 175-215 parts water, and 150-350 parts steel fiber.

[0055] In some embodiments provided in this application, the aforementioned second ultra-high performance concrete, by mass parts, comprises:

[0056] 900-1200 parts cementitious material, 700-1300 parts sand, 10-15 parts shrinkage reducer, 15-30 parts expansion agent, 30-50 parts water reducer, 170-205 parts water, and 5-40 parts steel fiber.

[0057] Preferably, the steel fibers are short, straight steel fibers with a diameter of 0.15mm-0.25mm and a length less than or equal to 80% of the diameter of the corresponding skeleton structure voids.

[0058] In this embodiment, the length of the steel fibers in the first ultra-high performance concrete is less than or equal to 80% of the diameter of the voids in the first skeleton structure. Similarly, the length of the steel fibers in the second ultra-high performance concrete is less than or equal to 80% of the diameter of the voids in the second skeleton structure.

[0059] In this embodiment, the workability of both the first ultra-high performance concrete and the second ultra-high performance concrete meets the following requirements: slump ≥ 260 mm, spread 650-850 mm, and V-shaped funnel passage time 5-12 s.

[0060] In this embodiment, the UHPC structure is designed in a gradient manner according to the different compressive and tensile performance requirements of different parts of the structure. By adjusting the regional distribution of coarse aggregate and steel fiber, the structure has graded strength and toughness while increasing the amount of coarse aggregate and reducing the amount of steel fiber. This achieves the overall performance of the structure while significantly reducing the material construction cost. In addition, through the UHPC matrix combination and steel fiber size optimization design, the first and second ultra-high performance concretes are both high-flowability UHPC slurry. This high-flowability UHPC slurry can pass smoothly through the voids in the coarse aggregate and achieve self-compacting filling.

[0061] Furthermore, the maximum particle size of the aforementioned sand is no greater than 3 mm, the fineness modulus is 2.0-2.3, and it has a continuous gradation. The aforementioned water-reducing agent is a polycarboxylate-based high-efficiency liquid water-reducing agent, the aforementioned shrinkage-reducing agent is an organic liquid shrinkage-reducing agent, and the aforementioned expanding agent is a calcium oxide-type liquid expanding agent.

[0062] In this embodiment, by adding organic shrinkage reducing agent and calcium oxide type expansion agent, the self-shrinkage deformation of UHPC matrix can be reduced by reducing the surface tension of matrix pore solution and generating expansive Ca(OH)2 crystals, respectively, thereby improving the volume stability and crack resistance of material and structure. The liquid phase form of shrinkage reducing agent and expansion agent is beneficial to reducing the viscosity of UHPC slurry and further improving its flowability. On the other hand, it is beneficial to the efficient dispersion of shrinkage reducing and expansion components to improve their shrinkage reduction efficiency.

[0063] This application also provides a method for preparing the above-mentioned coarse aggregate ultra-high performance concrete gradient structure, the preparation method specifically including the following steps:

[0064] S1. Place an isolation layer inside the precast mold, and pile coarse aggregate on both sides of the isolation layer to form the first skeleton and the second skeleton.

[0065] Preferably, the isolation layer is positioned such that the volume ratio of the precast mold on both sides of the isolation layer is 6-8:4-2, that is, the volume ratio of the second ultra-high performance concrete layer to the first ultra-high performance concrete layer formed subsequently is 6-8:4-2.

[0066] S2. Prepare the first ultra-high performance concrete and the second ultra-high performance concrete respectively.

[0067] S3. After placing a perforated plate on the upper end of the precast mold, the first ultra-high performance concrete and the second ultra-high performance concrete are injected into the precast molds on both sides of the isolation layer in stages through conduits to form the first ultra-high performance concrete layer and the second ultra-high performance concrete layer.

[0068] In this embodiment, the specific quality of high-strength, high-toughness, low-shrinkage, self-compacting ultra-high performance concrete and high-strength, low-cost, low-shrinkage, self-compacting ultra-high performance concrete is based on the complete filling of the pre-cast test mold, that is, the high-strength, high-toughness, low-shrinkage, self-compacting ultra-high performance concrete fills one side of the wire mesh mold, and the high-strength, low-cost, low-shrinkage, self-compacting ultra-high performance concrete fills the other side of the wire mesh mold.

[0069] In this embodiment, the perforated plate is preferably a perforated iron plate.

[0070] After forming the first and second ultra-high performance concrete layers, the process also includes covering the pre-cast test mold with a membrane and steam curing to obtain a coarse aggregate ultra-high performance concrete gradient structure.

[0071] Furthermore, the preparation of the first ultra-high performance concrete in step S2 above specifically includes:

[0072] First, the water-reducing agent, shrinkage-reducing agent, and expansion agent are mixed with a portion of the mixing water to obtain a mixed solution.

[0073] Next, the cementitious materials and sand for preparing the first ultra-high performance concrete are added to a mixer and mixed at medium speed. During the mixing process, the above-mentioned mixed solution and the remaining mixing water are added sequentially and mixed until a slurry is formed. The medium-speed mixing time is 50-200 seconds.

[0074] Then, stir at high speed, and add steel fibers slowly and evenly during the high-speed stirring process until the slurry and steel fibers are completely mixed. The high-speed stirring time is 100-300 seconds.

[0075] Finally, medium-speed mixing is performed to obtain the first ultra-high performance concrete. The medium-speed mixing time is 100-300 seconds.

[0076] Furthermore, the preparation of the second ultra-high performance concrete in step S2 above specifically includes:

[0077] First, the water-reducing agent, shrinkage-reducing agent, and expansion agent are mixed with a portion of the mixing water to obtain a mixed solution.

[0078] Next, the cementitious materials and sand for preparing the second ultra-high performance concrete are added to a mixer and mixed at medium speed. During the mixing process, the above-mentioned mixed solution and the remaining mixing water are added sequentially and mixed until a slurry is formed. The medium-speed mixing time is 50-200 seconds.

[0079] Then, stir at high speed, and add steel fibers slowly and evenly during the high-speed stirring process until the slurry and steel fibers are completely mixed. The high-speed stirring time is 100-300 seconds.

[0080] Finally, medium-speed mixing is performed to obtain the first ultra-high performance concrete. The medium-speed mixing time is 100-300 seconds.

[0081] Preferably, when simultaneously injecting the first ultra-high performance concrete and the second ultra-high performance concrete into the pre-cast test molds on both sides of the isolation layer through conduits in stages, the method further includes:

[0082] During each injection, the height difference between the concrete on both sides of the isolation layer should be less than or equal to 120% of the maximum diameter of the coarse aggregate; the height of each injected concrete should be less than or equal to 30% of the total height, and the interval between two injections should be greater than 3 minutes, so as to achieve step-by-step grouting.

[0083] Preferably, the conduit is a pressure hose. When the concrete is injected for the first time, the height of the outlet of the pressure hose from the bottom surface of the precast mold is greater than or equal to 90% of the maximum diameter of the coarse aggregate. When the concrete is injected for the first time, the height of the outlet of the pressure hose from the top surface of the previously injected concrete is greater than or equal to 90% of the maximum diameter of the coarse aggregate, that is, the height from the top surface of the precast mold to the top surface of the concrete is greater than or equal to 90% of the maximum diameter of the coarse aggregate.

[0084] In this embodiment, the concrete injection speed can be controlled by adjusting the pressure of the conduit, so that the height difference of the concrete on both sides of the isolation layer is less than or equal to 120% of the maximum diameter of the coarse aggregate.

[0085] Furthermore, on both sides of the isolation layer, there are no fewer than 3 pouring points on each side, that is, no fewer than 3 conduits on each side.

[0086] In one embodiment, the coarse aggregate is surface-treated before being piled up. Then, the coarse aggregate is piled up according to a model calculated by the software, with an isolation layer separating the coarse aggregate on both sides.

[0087] In this embodiment, an alkaline silica sol is uniformly sprayed onto the surface of the coarse aggregate using a sprayer to perform surface treatment on the coarse aggregate.

[0088] By spraying alkaline silica sol onto coarse aggregate, the nano-SiO2 in the silica sol has high pozzolanic activity and can react with hydration products to generate stable CSH gel, which improves the interfacial transition zone between coarse aggregate and paste and enhances the mechanical properties of concrete.

[0089] In this embodiment, the above-mentioned skeleton structure is designed using Diamond software and formed by stacking according to the coarse aggregate accumulation model. At the same time, grouting is used to pour high-strength, high-toughness, low-shrinkage, self-compacting ultra-high performance concrete and high-strength, low-cost, low-shrinkage, self-compacting ultra-high performance concrete into the coarse aggregate skeleton structure, forming a gradient structure with an impact-resistant, high-toughness layer and a deformation-resistant, high-bearing-capacity layer, so as to reduce the performance excess of ultra-high performance concrete and thus reduce the cost of ultra-high performance concrete structure.

[0090] The preparation method of this embodiment is applicable to the above-mentioned coarse aggregate ultra-high performance concrete gradient structures. The coarse aggregates are stacked sequentially according to the stacking model, and the coarse aggregates on both sides are separated with wire mesh to form a gradient stacking structure. This stacking method can effectively ensure the stability and porosity of the skeleton, as well as the permeability and filling properties of the self-compacting ultra-high performance concrete. The grouting casting process can, on the one hand, increase the coarse aggregate content in the concrete, give full play to the interlocking effect of the coarse aggregates, improve mechanical properties and volume stability, and reduce costs; on the other hand, it can reduce mixing time, prevent concrete segregation and bleeding, thereby reducing construction difficulty.

[0091] During pouring, a perforated iron plate is placed on top of the mold to stabilize the skeleton structure and ensure the stability of the coarse aggregate stack during the grouting process. At the same time, no fewer than three pouring points are set on both sides, and the distance between the guide pipe and the bottom of the mold or the already poured concrete is no less than 90% of the diameter of the coarse aggregate. This ensures that the concrete can effectively fill the gaps in the skeleton and prevents the concrete from accumulating at the bottom of the mold, thus smoothly achieving the step-by-step grouting process.

[0092] Optionally, the aforementioned conduits can be pre-placed evenly within the mold, or concrete can be injected through injection ports provided on the sidewalls of the mold.

[0093] In this embodiment, at the coarse aggregate level, the coarse aggregate incorporation method and graded stacking skeleton are designed to maximize the amount of coarse aggregate while ensuring good stability and permeability of the aggregate structure. Simultaneously, surface treatment of the coarse aggregate improves the interface transition zone between the coarse aggregate and the concrete matrix, further enhancing the mechanical properties of the coarse aggregate UHPC. At the steel fiber level, the regional distribution of steel fibers is adjusted to ensure the compressive strength of the UHPC while giving the structure graded toughness, forming a gradient distribution structure of steel fibers. At the matrix level, a synergistic shrinkage compensation composite technology using expansion agents and shrinkage reducing agents is used to reduce the early self-shrinkage of the UHPC matrix, improving the structural volume stability and crack resistance. Regarding the structural gradient design, a modular gradient design is implemented based on the stress characteristics of different parts, allowing for on-demand design of structural strength and toughness, further reducing material construction costs while ensuring overall structural performance. In terms of the manufacturing process, pre-placed aggregate and grouting casting processes are adopted to fully utilize the skeleton rigidity effect and high permeability of the stacked aggregate, achieving controllability and convenience in the construction process.

[0094] Preferably, the first ultra-high performance concrete is a high-strength, high-toughness, low-shrinkage, self-compacting ultra-high performance concrete, and the second ultra-high performance concrete is a high-strength, low-cost, low-shrinkage, self-compacting ultra-high performance concrete.

[0095] The technical solutions provided in this application will be described in detail below with reference to the embodiments.

[0096] Example 1

[0097] This embodiment provides a coarse aggregate ultra-high performance concrete gradient structure with compressive strength on the left and tensile strength on the right, and its preparation method. The gradient structure, from left to right, includes a second ultra-high performance concrete layer, an isolation layer, and a first ultra-high performance concrete layer. The gradient structure exhibits a gradient distribution in the horizontal direction, with the volume ratio of the second ultra-high performance concrete layer to the first ultra-high performance concrete layer being 6:4.

[0098] The gradient structure comprises the following raw materials: ordinary Portland cement (Huaxin Cement Co., Ltd., Huangshi, Hubei), microsilica powder (Lanxing Silicon Materials Co., Ltd., Lanzhou, Gansu), Class I fly ash (Huaneng Yangluo Power Plant, Wuhan, Hubei), polycarboxylate liquid water-reducing agent (Jiangsu Subote New Materials Co., Ltd., Nanjing, Jiangsu), UEA expansion agent (Wuhan Sanyuan Special Building Materials Co., Ltd., Wuhan, Hubei), SBT-SRA(I) shrinkage reducer (Jiangsu Subote New Materials Co., Ltd., Nanjing, Jiangsu), river sand (Hubei Jiukesong Quartz Stone Co., Ltd., Huanggang, Hubei), granite crushed stone (Hubei Jiukesong Quartz Stone Co., Ltd., Huanggang, Hubei), short straight steel fibers (Chengdu Keliang Building Materials Co., Ltd., Chengdu, Sichuan), and alkaline silica sol (Linyi Zhixuan New Materials Co., Ltd., Linyi, Shandong). The river sand has a particle size distribution of 0.6mm-2.7mm and a fineness modulus of 2.1; the granite crushed stone has a hardness of 6, uses a continuous gradation of 18-23mm, a compressive strength of 166MPa, and a needle-like / flaky particle content of 5% of the total.

[0099] The above preparation method includes the following steps:

[0100] Step 1: Divide the pre-cast test mold into two parts in a 6:4 ratio, separated by wire mesh 3. Design a coarse aggregate stacking model using Diamond software, and stack the granite crushed stone 4, which has been surface-treated with alkaline silica sol, into the mold according to the model. The larger part is stacked with 2096 pieces of crushed stone, and the smaller part is stacked with 1048 pieces of crushed stone.

[0101] Step 2: Prepare high-strength, high-toughness, low-shrinkage self-compacting ultra-high performance concrete and high-strength, low-cost, low-shrinkage self-compacting ultra-high performance concrete. The specific mass of both types of ultra-high-strength, high-toughness, low-shrinkage self-compacting ultra-high performance concrete is determined by completely filling the pre-cast molds. Specifically, high-strength, high-toughness, low-shrinkage self-compacting ultra-high performance concrete fills the right-side mold of the wire mesh, while high-strength, low-cost, low-shrinkage self-compacting ultra-high performance concrete fills the left-side mold of the wire mesh. The mass ratio of the two is the ratio of their filling amounts.

[0102] The aforementioned high-strength, high-toughness, low-shrinkage, self-compacting ultra-high-performance concrete, by weight, comprises: 823 parts cement, 122 parts silica fume, 95 parts fly ash, 896 parts sand, 13 parts shrinkage reducer, 23 parts expansion agent, 32 parts water-reducing agent, 191 parts water, and 234 parts steel fiber.

[0103] The aforementioned high-strength, low-cost, low-shrinkage, self-compacting ultra-high-performance concrete, by weight, comprises: 883 parts cement, 136 parts silica fume, 102 parts fly ash, 914 parts sand, 13 parts shrinkage-reducing agent, 23 parts expansion agent, 32 parts water-reducing agent, 185 parts water, and 38 parts steel fiber. Among these, cement, silica fume, and fly ash are gelling materials.

[0104] To prepare high-strength, high-toughness, low-shrinkage self-compacting ultra-high-performance concrete or high-strength, low-cost, low-shrinkage self-compacting ultra-high-performance concrete: the weighed cementitious materials and sand are added to a mixer and mixed at medium speed for 125 seconds. During the medium-speed mixing process, an aqueous solution of high-efficiency water-reducing agent, shrinkage-reducing agent, expansion agent, and a portion of water is added, along with the remaining water, and the mixture is stirred until a paste is formed. Then, the mixture is stirred at high speed for 195 seconds, and steel fiber 5 is added during the high-speed mixing process. Finally, the mixture is stirred at medium speed for 245 seconds to obtain two different types of self-compacting ultra-high-performance concrete.

[0105] Step 3: After placing a perforated iron plate 6 on the top of the mold, simultaneously inject high-strength, high-toughness, low-shrinkage, self-compacting ultra-high performance concrete into the right side of the wire mesh, i.e. the side with less coarse aggregate, and inject high-strength, low-cost, low-shrinkage, self-compacting ultra-high performance concrete into the left side of the wire mesh, i.e. the side with more coarse aggregate.

[0106] The system includes six injection conduits. Before placing the aggregate, three conduits on each side of the wire mesh are pre-installed evenly within the mold. The concrete injection speed on both sides is controlled to ensure that the height difference does not exceed the maximum diameter of the coarse aggregate. Each pour is 25% of the total height. After each pour, the conduit outlet is moved upwards to above the top surface of the concrete within the mold, with the outlet height from the top surface of the concrete within the mold not less than 90% of the maximum diameter of the coarse aggregate. The interval between two pours is 3.5 minutes to obtain the first ultra-high performance concrete layer 1 and the second ultra-high performance concrete layer 2.

[0107] Step 4: Cover the mold with a film and steam cure to obtain a gradient structure of ultra-high performance concrete with coarse aggregate, resistant to compression on the left and tensile strength on the right, as shown in the figure. Figure 1 As shown.

[0108] Examples 2 and 3 are prepared in a similar manner to Example 1, using the same raw materials but with different proportions. The specific differences are described below.

[0109] Example 2

[0110] In Example 2, the mass ratio of high-strength, high-toughness, low-shrinkage, self-compacting ultra-high performance concrete to high-strength, low-cost, low-shrinkage, self-compacting ultra-high performance concrete is the ratio of the filling amount.

[0111] The difference between Example 2 and Example 1 is as follows:

[0112] The high-strength, high-toughness, low-shrinkage, self-compacting ultra-high-performance concrete, by weight, includes: 732 parts cement, 95 parts silica fume, 73 parts fly ash, 700 parts sand, 10 parts shrinkage reducer, 15 parts expansion agent, 20 parts water-reducing agent, 175 parts water, and 150 parts steel fiber.

[0113] The high-strength, low-cost, low-shrinkage, self-compacting, ultra-high-performance concrete, by weight, includes: 749 parts cement, 82 parts silica fume, 69 parts fly ash, 700 parts sand, 10 parts shrinkage reducer, 15 parts expansion agent, 30 parts water-reducing agent, 170 parts water, and 5 parts steel fiber.

[0114] The rest is the same as in Example 1.

[0115] Example 3

[0116] In Example 3, the mass ratio of high-strength, high-toughness, low-shrinkage, self-compacting ultra-high performance concrete to high-strength, low-cost, low-shrinkage, self-compacting ultra-high performance concrete is the ratio of the filling amount.

[0117] The difference between Example 3 and Example 1 is as follows:

[0118] The high-strength, high-toughness, low-shrinkage, self-compacting ultra-high-performance concrete, by weight, includes: 973 parts cement, 126 parts silica fume, 101 parts fly ash, 1300 parts sand, 15 parts shrinkage reducer, 30 parts expansion agent, 50 parts water-reducing agent, 215 parts water, and 350 parts steel fiber.

[0119] High-strength, low-cost, low-shrinkage, self-compacting, ultra-high-performance concrete, by weight, includes: 980 parts cement, 123 parts silica fume, 97 parts fly ash, 1300 parts sand, 15 parts shrinkage reducer, 30 parts expansion agent, 50 parts water-reducing agent, 205 parts water, and 40 parts steel fiber.

[0120] The rest is the same as in Example 1.

[0121] Comparative Examples 1-4 use the same raw materials as Example 1, but different preparation methods, as described below.

[0122] Comparative Example 1

[0123] The difference between this comparative example and Example 1 is that:

[0124] Comparative Example 1 includes the following preparation steps:

[0125] Step 1: Weigh the following raw materials by mass: 3079 parts cement, 420 parts silica fume, 356 parts fly ash, 3360 parts sand, 49 parts shrinkage reducer, 86 parts expansion agent, 120 parts water-reducing agent, 716 parts water, and 878 parts steel fiber.

[0126] Step 2: Add cement, silica fume, and fly ash, which serve as cementitious materials, along with sand, to a mixer and mix at medium speed for 125 seconds. During the medium-speed mixing process, add an aqueous solution of high-efficiency water-reducing agent, shrinkage-reducing agent, expansion agent, and a portion of water. Add the remaining water during the mixing process and mix until a paste is formed. Then mix at high speed for 195 seconds and add steel fibers during the high-speed mixing process. Finally, mix at medium speed for 245 seconds to obtain high-strength, high-toughness, low-shrinkage, self-compacting, ultra-high-performance concrete.

[0127] Step 3: Pour the concrete into the mold, then cover the mold with a film and steam cure it to obtain Comparative Example 1.

[0128] The rest is the same as in Example 1, including that the volume of the ultra-high performance concrete in Comparative Example 1 is the same as the volume of the coarse aggregate ultra-high performance concrete gradient structure in Example 1.

[0129] Comparative Example 2

[0130] The difference between this comparative example and Example 1 is that:

[0131] Comparative Example 2 includes the following preparation steps:

[0132] Step 1: Weigh the following raw materials by mass: 3206 parts cement, 540 parts silica fume, 454 parts fly ash, 3360 parts sand, 49 parts shrinkage reducer, 86 parts expansion agent, 120 parts water-reducing agent, 698 parts water, and 94 parts steel fiber.

[0133] Step 2: Add cementitious materials and sand to the mixer and mix at medium speed for 125 seconds. During the medium-speed mixing process, add an aqueous solution of high-efficiency water-reducing agent, shrinkage-reducing agent, expansion agent and a portion of water. Add the remaining water during the mixing process and mix until a slurry is formed. Then mix at high speed for 195 seconds and add steel fibers during the high-speed mixing process. Finally, mix at medium speed for 245 seconds to obtain high-strength, low-cost, low-shrinkage, self-compacting, ultra-high-performance concrete.

[0134] Step 3: Pour the concrete into the mold, then cover the mold with a film and steam cure it to obtain Comparative Example 2.

[0135] The rest is the same as in Example 1.

[0136] Comparative Example 3

[0137] The difference between this comparative example and Example 1 is that:

[0138] Comparative Example 3 includes the following preparation steps:

[0139] Step 1: Weigh the following raw materials by mass: 2052 parts cement, 280 parts silica fume, 238 parts fly ash, 2240 parts sand, 2620 parts crushed stone, 33 parts shrinkage reducer, 58 parts expansion agent, 80 parts water-reducing agent, 478 parts water, and 585 parts steel fiber.

[0140] Step 2: Add cementitious materials, sand, and crushed stone to the mixer and mix at medium speed for 125 seconds. During the medium-speed mixing process, add an aqueous solution of high-efficiency water-reducing agent, shrinkage-reducing agent, expansion agent, and a portion of water. Add the remaining water during the mixing process and mix until a slurry is formed. Then mix at high speed for 195 seconds and add steel fibers during the high-speed mixing process. Finally, mix at medium speed for 245 seconds to obtain high-strength, high-toughness, low-shrinkage coarse aggregate ultra-high performance concrete.

[0141] Step 3: Pour the concrete into the mold, then cover the mold with a film and steam cure it to obtain Comparative Example 3.

[0142] The rest is the same as in Example 1.

[0143] Comparative Example 4

[0144] The difference between this comparative example and Example 1 is that:

[0145] The comparative example includes the following preparation steps:

[0146] Step 1: Weigh the following raw materials by mass: 2129 parts cement, 359 parts silica fume, 301 parts fly ash, 2231 parts sand, 2865 parts crushed stone, 32 parts shrinkage reducer, 57 parts expansion agent, 80 parts water-reducing agent, 463 parts water, and 62 parts steel fiber.

[0147] Step 2: Add cementitious materials, sand, and crushed stone to the mixer and mix at medium speed for 125 seconds. During the medium-speed mixing process, add an aqueous solution of high-efficiency water-reducing agent, shrinkage-reducing agent, expansion agent, and a portion of water. Add the remaining water during the mixing process and mix until a slurry is formed. Then, mix at high speed for 195 seconds and add steel fibers during the high-speed mixing process. Finally, mix at medium speed for 245 seconds to obtain high-strength, low-cost, low-shrinkage coarse aggregate ultra-high performance concrete.

[0148] Step 3: Pour the concrete into the mold, then cover the mold with a film and steam cure it to obtain Comparative Example 4.

[0149] The rest is the same as in Example 1.

[0150] The spread of UHPC paste was determined according to GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures". The compressive, flexural, and tensile strengths, and modulus of elasticity of UHPC specimens were determined according to GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The impact and abrasion resistance of UHPC specimens was determined according to "Test Procedures for Hydraulic Concrete" (DL / T 5150-2017). The shrinkage (non-contact method) of UHPC specimens was determined according to GB / T 50082-2009 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete".

[0151] Table 1 shows a performance comparison between Examples 1-3 and Comparative Examples 1-4. The compressive strength development of Examples 1 and Comparative Examples 1-4 is shown in Table 1. Figure 2 The development of flexural strength is seen Figure 3 The development of tensile strength is seen Figure 4 .

[0152] Table 1 Performance comparison of Examples 1-3 and Comparative Examples 1-4

[0153]

[0154] As shown in Table 1:

[0155] Compared with the high-strength, high-toughness, low-shrinkage self-compacting ultra-high performance concrete prepared in Comparative Example 1, the coarse aggregate ultra-high performance concrete gradient structure prepared in Example 1 maintains the same level of mechanical properties such as compressive strength, flexural strength, and tensile strength, while increasing impact and abrasion resistance by 35%, volume stability by 54%, and reducing cost by 50%.

[0156] Compared with the high-strength, low-cost, low-shrinkage self-compacting ultra-high performance concrete prepared in Comparative Example 2, the coarse aggregate ultra-high performance concrete gradient structure prepared in Example 1 has an 8% increase in compressive strength, a 97% increase in flexural strength, a 118% increase in tensile strength, a 48% increase in impact and abrasion resistance, a 58% increase in volume stability, and a 21% reduction in cost.

[0157] Compared with the high-strength, high-toughness, low-shrinkage coarse aggregate ultra-high performance concrete gradient structure prepared in Comparative Example 3, the elastic modulus of the coarse aggregate ultra-high performance concrete gradient structure prepared in Example 1 was slightly improved, its compressive strength was increased by 7%, its flexural strength by 44%, its tensile strength by 38%, its impact and abrasion resistance by 22%, its volume stability by 24%, its workability by 55%, and its cost was reduced by 13%.

[0158] Compared with the high-strength, low-cost, low-shrinkage coarse aggregate ultra-high performance concrete gradient structure prepared in Comparative Example 4, the elastic modulus of the coarse aggregate ultra-high performance concrete gradient structure prepared in Example 1 was slightly improved, its compressive strength was increased by 10%, its flexural strength by 135%, its tensile strength by 172%, its impact and abrasion resistance by 13%, its volume stability by 39%, and its workability by 69%.

[0159] The results show that the gradient structure of ultra-high performance concrete with coarse aggregate on the left and tensile strength on the right in this embodiment and its preparation method can combine the performance advantages of ordinary ultra-high performance concrete and ordinary coarse aggregate ultra-high performance concrete, so that it has excellent mechanical properties, workability, volume stability and impact resistance, as well as low preparation cost. It realizes the performance design of coarse aggregate ultra-high performance concrete in the left and right directions as needed, and greatly improves its application range.

[0160] Example 4

[0161] The difference between Example 4 and Example 1 is that Example 4 provides a coarse aggregate ultra-high performance concrete gradient structure with upper compressive strength and lower tensile strength, and its preparation method. This gradient structure, from top to bottom, includes a second ultra-high performance concrete layer, an isolation layer, and a first ultra-high performance concrete layer. The volume ratio of the second ultra-high performance concrete layer to the first ultra-high performance concrete layer is 8:2. Other aspects, including the raw materials used and the testing methods, are consistent with Example 1.

[0162] The preparation steps for the above-mentioned coarse aggregate ultra-high performance concrete gradient structure are as follows:

[0163] Step 1: Divide the pre-cast test mold into two parts at an 8:2 ratio, separated by wire mesh 3. Design a coarse aggregate stacking model using Diamond software, and stack granite crushed stone 4, which has been surface-treated with alkaline silica sol, into the mold according to the model. The larger part is stacked with 6475 parts of coarse aggregate, and the smaller part is stacked with 925 parts of coarse aggregate.

[0164] Step 2: Prepare high-strength, high-toughness, low-shrinkage self-compacting ultra-high performance concrete and high-strength, low-cost, low-shrinkage self-compacting ultra-high performance concrete. The mass ratio of the high-strength, high-toughness, low-shrinkage self-compacting ultra-high performance concrete to the high-strength, low-cost, low-shrinkage self-compacting ultra-high performance concrete is the ratio of their filler amounts.

[0165] The high-strength, high-toughness, low-shrinkage, self-compacting ultra-high-performance concrete, by weight, includes: 854 parts cement, 144 parts silica fume, 112 parts fly ash, 913 parts sand, 13 parts shrinkage reducer, 25 parts expansion agent, 30 parts water-reducing agent, 195 parts water, and 273 parts steel fiber.

[0166] The high-strength, low-cost, low-shrinkage, self-compacting, ultra-high-performance concrete, by weight, includes: 879 parts cement, 152 parts silica fume, 134 parts fly ash, 863 parts sand, 13 parts shrinkage reducer, 20 parts expansion agent, 32 parts water-reducing agent, 183 parts water, and 32 parts steel fiber.

[0167] When preparing high-strength, high-toughness, low-shrinkage self-compacting ultra-high-performance concrete or high-strength, low-cost, low-shrinkage self-compacting ultra-high-performance concrete: add cementitious materials and sand to a mixer, mix at medium speed for 115 seconds, and add an aqueous solution of high-efficiency water-reducing agent, shrinkage-reducing agent, expansion agent and a portion of water, as well as the remaining water, and mix until a paste is formed; then mix at high speed for 245 seconds, and add steel fiber 5 during the high-speed mixing process, and finally mix at medium speed for 275 seconds to obtain two different self-compacting ultra-high-performance concretes.

[0168] Step 3: After placing a perforated iron plate on top of the mold, simultaneously inject high-strength, high-toughness, low-shrinkage, self-compacting ultra-high-performance concrete into the right side of the wire mesh (the side with less coarse aggregate) and inject high-strength, low-cost, low-shrinkage, self-compacting ultra-high-performance concrete into the left side of the wire mesh (the side with more coarse aggregate).

[0169] The system includes six injection conduits. Before placing the aggregate, three conduits on each side of the wire mesh are pre-installed evenly within the mold. The concrete injection speed on both sides is controlled so that the height difference does not exceed 110% of the maximum diameter of the coarse aggregate. Each concrete pour is 20% of the total height. After each pour, the conduit outlet is moved upwards to above the top surface of the concrete within the mold, with the outlet height from the top surface of the concrete within the mold not less than 90% of the maximum diameter of the coarse aggregate. The interval between two pours is 4 minutes to obtain the first ultra-high performance concrete layer 1 and the second ultra-high performance concrete layer 2.

[0170] Step 4: Remove the porous iron plate, seal the top of the mold, and after the slurry inside the mold has solidified and hardened, lay the mold down with the side containing more coarse aggregate facing upwards. Then, perform steam curing with a membrane to obtain a gradient structure of ultra-high performance concrete with coarse aggregate that is resistant to compression on the top and tensile strength on the bottom. Figure 5 As shown.

[0171] Examples 5 and 6 are prepared in a similar manner to Example 4, using the same raw materials but with different proportions. The specific differences are described below.

[0172] Example 5

[0173] The difference between Example 5 and Example 4 is as follows:

[0174] The high-strength, high-toughness, low-shrinkage, self-compacting ultra-high-performance concrete, by weight, includes: 712 parts cement, 100 parts silica fume, 88 parts fly ash, 700 parts sand, 10 parts shrinkage reducer, 15 parts expansion agent, 20 parts water-reducing agent, 175 parts water, and 150 parts steel fiber.

[0175] The high-strength, low-cost, low-shrinkage, self-compacting, ultra-high-performance concrete, by weight, includes: 676 parts cement, 117 parts silica fume, 107 parts fly ash, 700 parts sand, 10 parts shrinkage reducer, 15 parts expansion agent, 20 parts water-reducing agent, 170 parts water, and 5 parts steel fiber.

[0176] The rest is the same as in Example 4.

[0177] Example 6

[0178] The difference between Example 6 and Example 4 is as follows:

[0179] The high-strength, high-toughness, low-shrinkage, self-compacting ultra-high-performance concrete, by weight, includes: 947 parts cement, 136 parts silica fume, 117 parts fly ash, 1300 parts sand, 15 parts shrinkage reducer, 30 parts expansion agent, 50 parts water-reducing agent, 215 parts water, and 350 parts steel fiber.

[0180] The high-strength, low-cost, low-shrinkage, self-compacting, ultra-high-performance concrete, by weight, includes: 903 parts cement, 155 parts silica fume, 142 parts fly ash, 1300 parts sand, 15 parts shrinkage reducer, 30 parts expansion agent, 30 parts water-reducing agent, 205 parts water, and 40 parts steel fiber.

[0181] The rest is the same as in Example 4.

[0182] Comparative Examples 5-8 use the same raw materials as Example 4, but the preparation methods are different. The specific differences are described below.

[0183] Comparative Example 5

[0184] The difference between this comparative example and Example 4 is that:

[0185] Comparative Example 5 includes the following preparation steps:

[0186] Step 1: Weigh the following raw materials by mass fraction: 4586 parts cement, 773 parts silica fume, 601 parts fly ash, 4903 parts sand, 70 parts shrinkage reducer, 134 parts expansion agent, 161 parts water-reducing agent, 1047 parts water, and 172 parts steel fiber.

[0187] Step 2: Add cement, silica fume, and fly ash, which serve as cementitious materials, along with sand, to a mixer and mix at medium speed for 115 seconds. During the medium-speed mixing process, add an aqueous solution of high-efficiency water-reducing agent, shrinkage-reducing agent, and expansion agent mixed with a portion of water, as well as the remaining water, and mix until a paste is formed. Then mix at high speed for 245 seconds, and add steel fibers during the high-speed mixing process. Finally, mix at medium speed for 275 seconds to obtain high-strength, high-toughness, low-shrinkage, self-compacting, ultra-high-performance concrete.

[0188] Step 3: Pour the concrete into the mold, then cover the mold with a film and steam cure it to obtain Comparative Example 5.

[0189] The rest is the same as in Example 4, including that the volume of the ultra-high performance concrete in Comparative Example 5 is the same as the volume of the coarse aggregate ultra-high performance concrete gradient structure in Example 4.

[0190] Comparative Example 6

[0191] The difference between this comparative example and Example 4 is that:

[0192] Comparative Example 6 includes the following preparation steps:

[0193] Step 1: Weigh the following raw materials by mass fraction: 5340 parts cement, 923 parts silica fume, 814 parts fly ash, 5243 parts sand, 79 parts shrinkage reducer, 122 parts expansion agent, 194 parts water-reducing agent, 1112 parts water, and 194 parts steel fiber.

[0194] Step 2: Add cementitious materials and sand to the mixer and mix at medium speed for 115 seconds. During the medium-speed mixing process, add an aqueous solution of high-efficiency water-reducing agent, shrinkage-reducing agent, expansion agent and a portion of water, as well as the remaining water. Mix until a slurry is formed, then mix at high speed for 245 seconds. During the high-speed mixing process, add steel fibers and finally mix at medium speed for 275 seconds to obtain high-strength, low-cost, low-shrinkage, self-compacting, ultra-high-performance concrete.

[0195] Step 3: Pour the concrete into the mold, then cover the mold with a film and steam cure it to obtain Comparative Example 6.

[0196] The rest is the same as in Example 4.

[0197] Comparative Example 7

[0198] The difference between this comparative example and Example 4 is that:

[0199] Comparative Example 7 includes the following preparation steps:

[0200] Step 1: Weigh the following raw materials by mass fraction: 2967 parts cement, 513 parts silica fume, 452 parts fly ash, 2912 parts sand, 9018 parts crushed stone, 44 parts shrinkage reducer, 68 parts expansion agent, 108 parts water-reducing agent, 618 parts water, and 108 parts steel fiber.

[0201] Step 2: Add cementitious materials, sand, and crushed stone to the mixer and mix at medium speed for 115 seconds. During the medium-speed mixing process, add an aqueous solution of high-efficiency water-reducing agent, shrinkage-reducing agent, expansion agent, and a portion of water, as well as the remaining water. Mix until a slurry is formed, then mix at high speed for 245 seconds. During the high-speed mixing process, add steel fibers and finally mix at medium speed for 275 seconds to obtain high-strength, high-toughness, low-shrinkage coarse aggregate ultra-high performance concrete.

[0202] Step 3: Pour the concrete into the mold, then cover the mold with a film and steam cure it to obtain Comparative Example 7.

[0203] The rest is the same as in Example 2.

[0204] Comparative Example 8

[0205] The difference between this comparative example and Example 4 is that:

[0206] Comparative Example 8 includes the following preparation steps:

[0207] Step 1: Weigh the following raw materials by mass fraction: 4270 parts cement, 720 parts silica fume, 560 parts fly ash, 4565 parts sand, 4625 parts crushed stone, 65 parts shrinkage reducer, 125 parts expansion agent, 150 parts water-reducing agent, 975 parts water, and 160 parts steel fiber.

[0208] Step 2: Add cementitious materials, sand, and crushed stone to the mixer and mix at medium speed for 115 seconds. During the medium-speed mixing process, add an aqueous solution of high-efficiency water-reducing agent, shrinkage-reducing agent, expansion agent, and a portion of water, as well as the remaining water. Mix until a slurry is formed, then mix at high speed for 245 seconds. During the high-speed mixing process, add steel fibers and finally mix at medium speed for 275 seconds to obtain high-strength, low-cost, low-shrinkage coarse aggregate ultra-high performance concrete.

[0209] Step 3: Pour the concrete into the mold, then cover the mold with a film and steam cure it to obtain Comparative Example 4.

[0210] The rest is the same as in Example 4.

[0211] Table 2 shows a performance comparison between Examples 4-6 and Comparative Examples 5-8. The compressive strength development of Examples 4 and Comparative Examples 5-8 is shown in Table 2. Figure 6 The development of flexural strength is seen Figure 7 The development of tensile strength is seen Figure 8 .

[0212] Table 2. Performance Comparison of Examples 4-6 and Comparative Examples 5-8

[0213]

[0214]

[0215] As shown in Table 2:

[0216] Compared with the high-strength, high-toughness, low-shrinkage self-compacting ultra-high performance concrete prepared in Comparative Example 5, the coarse aggregate ultra-high performance concrete gradient structure prepared in Example 4 maintains the same level of mechanical properties such as compressive strength, flexural strength, and tensile strength, while increasing impact and abrasion resistance by 32%, volume stability by 52%, and reducing cost by 54%.

[0217] Compared with the high-strength, low-cost, low-shrinkage self-compacting ultra-high performance concrete prepared in Comparative Example 6, the coarse aggregate ultra-high performance concrete gradient structure prepared in Example 4 has a 97% increase in flexural strength, a 93% increase in tensile strength, a 39% increase in impact and abrasion resistance, a 57% increase in volume stability, and a 19% reduction in cost.

[0218] Compared with the high-strength, high-toughness, low-shrinkage coarse aggregate ultra-high performance concrete gradient structure prepared in Comparative Example 7, the elastic modulus of the coarse aggregate ultra-high performance concrete gradient structure prepared in Example 4 was slightly improved, its compressive strength was increased by 10%, its flexural strength by 40%, its tensile strength by 32%, its impact and abrasion resistance by 22%, its volume stability by 18%, its workability by 53%, and its cost was reduced by 8%.

[0219] Compared with the high-strength, low-cost, low-shrinkage coarse aggregate ultra-high performance concrete gradient structure prepared in Example 4, the elastic modulus of the coarse aggregate ultra-high performance concrete prepared in Example 8 was slightly improved, its compressive strength increased by 14%, its flexural strength increased by 121%, its tensile strength increased by 129%, its impact and abrasion resistance increased by 15%, its volume stability increased by 32%, and its workability increased by 73%.

[0220] The results show that the gradient structure of coarse aggregate ultra-high performance concrete with upper compressive strength and lower tensile strength in this embodiment and its preparation method can combine the performance advantages of ordinary ultra-high performance concrete and ordinary coarse aggregate ultra-high performance concrete, so that it has excellent mechanical properties, workability, volume stability and impact resistance, as well as low preparation cost. It realizes the performance design of coarse aggregate ultra-high performance concrete in the upper and lower directions as needed, and greatly improves its application range.

[0221] In this embodiment, a gradient structure is prepared by adjusting the local steel fiber content according to the structural stress characteristics. The gradient design process, pre-placed aggregate, and grouting pouring process are combined to meet the overall performance requirements of the structure and ensure the construction quality of concrete. At the same time, the coarse aggregate content is further increased, and the construction cost of ultra-high performance concrete structure is further reduced. This achieves the synergistic improvement of material design and economic benefits, solves the contradiction between high aggregate content and insufficient mechanical properties of concrete, and realizes the synergistic improvement of economic efficiency and structural performance, which is conducive to expanding its practical engineering application scope.

[0222] In the description of this specification, the references to terms such as "one embodiment / mode," "some embodiments / modes," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment / mode or example is included in at least one embodiment / mode or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment / mode or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments / modes or examples. Furthermore, without contradiction, those skilled in the art can combine and integrate the different embodiments / modes or examples described in this specification, as well as the features of different embodiments / modes or examples.

[0223] It should be noted that in this application, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element. In this application, "a plurality of" means at least two, such as two, three, etc., unless otherwise expressly specified.

[0224] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A gradient structure of ultra-high performance concrete with coarse aggregate, characterized in that, The coarse aggregate ultra-high performance concrete gradient structure comprises, in sequence: The first ultra-high performance concrete layer includes a first skeleton formed of coarse aggregate and a first ultra-high performance concrete layer that encapsulates the first skeleton. Isolation layer; The second ultra-high performance concrete layer includes a second skeleton formed of coarse aggregate and a second ultra-high performance concrete layer that encapsulates the second skeleton. The isolation layer is a wire mesh, and the mesh diameter is less than or equal to 60% of the minimum diameter of the aggregate. The coarse aggregate content of the first skeleton is less than that of the second skeleton. The coarse aggregate of both the first and second skeletons is cubically loosely packed, and the void diameter of the skeleton structure is greater than or equal to 8 mm. The first ultra-high performance concrete, by mass parts, comprises: 900-1200 parts cementitious material, 700-1300 parts sand, 10-15 parts shrinkage reducer, 15-30 parts expansion agent, 20-50 parts water-reducing agent, 175-215 parts water, and 150-350 parts steel fiber. The second ultra-high performance concrete, by weight, comprises: 900-1200 parts cementitious material, 700-1300 parts sand, 10-15 parts shrinkage reducer, 15-30 parts expansion agent, 30-50 parts water reducer, 170-205 parts water, and 5-40 parts steel fiber. The steel fibers are short, straight steel fibers with a diameter of 0.15mm-0.25mm and a length less than or equal to 80% of the diameter of the corresponding skeletal structure voids. The coarse aggregate ultra-high performance concrete gradient structure is prepared by the following method: An isolation layer is placed inside the precast mold, and coarse aggregate is piled up on both sides of the isolation layer to form the first skeleton and the second skeleton. First ultra-high performance concrete and second ultra-high performance concrete were prepared respectively; After placing a perforated plate on the upper end of the precast mold, the first ultra-high performance concrete and the second ultra-high performance concrete are simultaneously injected into the precast molds on both sides of the isolation layer through conduits in stages to form the first ultra-high performance concrete layer and the second ultra-high performance concrete layer.

2. The coarse aggregate ultra-high performance concrete gradient structure as described in claim 1, characterized in that, The coarse aggregate has a hardness ≥6, a compressive strength ≥150MPa, a gradation of 15-25mm continuous gradation, and a needle-like and flaky content of 2-8%.

3. A method for preparing the coarse aggregate ultra-high performance concrete gradient structure according to claim 1, characterized in that, The preparation method includes: An isolation layer is placed inside the precast mold, and coarse aggregate is piled up on both sides of the isolation layer to form the first skeleton and the second skeleton. First ultra-high performance concrete and second ultra-high performance concrete were prepared respectively; After placing a perforated plate on the upper end of the precast mold, the first ultra-high performance concrete and the second ultra-high performance concrete are simultaneously injected into the precast molds on both sides of the isolation layer through conduits in stages to form the first ultra-high performance concrete layer and the second ultra-high performance concrete layer.

4. The preparation method according to claim 3, characterized in that, Simultaneously, when the first ultra-high performance concrete and the second ultra-high performance concrete are injected into the pre-cast test molds on both sides of the isolation layer in stages through conduits, the process also includes: During each injection, the height difference between the concrete on both sides of the isolation layer should be less than or equal to 120% of the maximum diameter of the coarse aggregate; Each injection of concrete should be less than or equal to 30% of the total height, and the interval between two injections should be greater than 3 minutes.

5. The preparation method according to claim 4, characterized in that: The conduit is a pressure hose; During the first concrete injection, the height of the outlet of the pressure hose from the bottom surface of the precast mold shall be greater than or equal to 90% of the maximum diameter of the coarse aggregate. In each subsequent injection, the height of the outlet of the pressure hose from the top surface of the previously injected concrete shall be greater than or equal to 90% of the maximum diameter of the coarse aggregate.

6. The preparation method according to claim 3, characterized in that, Before piling up coarse aggregate, the process also includes: Alkaline silica sol is evenly sprayed onto the surface of coarse aggregate using a sprayer to perform surface treatment on the coarse aggregate.

Citation Information

Patent Citations

  • Ultra-high performance concrete gradient composite structure and preparation method thereof

    CN115717347A

  • Single-layer preset coarse aggregate grouting type UHPC (Ultra High Performance Concrete) board, functionally gradient high-performance cement-based fiber composite board and preparation method

    CN117247255A